IMPROVEMENT OF THE MANAGEMENT MECHANISM OF INVESTMENT PROJECTS IN THE DEVELOPMENT OF THE EDUCATION SECTOR (Marketing Journal, 2025)
This research aims to enhance the management mechanisms of investment projects in the education sector. The education system plays a vital role in the economic and social progress of a nation, making it essential to attract and effectively manage investmen ts in educational initiatives. The paper offers recommendations for improving the effectiveness of education -related investment projects, focusing on both financial and managerial aspects. It examines the main challenges faced in managing educational inves tments, such as resource allocation, project planning, and monitoring, while also evaluating the long -term and short -term benefits these projects bring to the education system. The study highlights the importance of adopting modern management approaches an d leveraging global experiences to solve these challenges.
Keywords: education sector; investment projects; investment management; efficiency; education in Uzbekistan; public -private partnerships; private sector; international funding; education infrastructure; innovative technologies; digitalization in education; foreign investments; human capital; education investments; monitoring system; quality improvement in education; educational economics; bureaucratic barriers; financial effectiveness; reg ional equality